A Novel Nonsense Mutation of the AGL Gene in a Romanian Patient with Glycogen Storage Disease Type IIIa - Anca Zimmermann; Heidi Rossmann; Simona Bucerzan; Paula Grigorescu-Sido (Case Reports in Genetics)
Background. Glycogen storage disease type III (GSDIII) is a rare metabolic disorder with autosomal recessive inheritance, caused by deficiency of the glycogen debranching enzyme. There is a high phenotypic variability due to different mutations in the AGL gene. Methods and Results. We describe a 2.3-year-old boy from a nonconsanguineous Romanian family, who presented with severe hepatomegaly with fibrosis, mild muscle weakness, cardiomyopathy, ketotic fasting hypoglycemia, increased transaminases, creatine phosphokinase, and combined hyperlipoproteinemia. GSD type IIIa was suspected. Accordingly, genomic DNA of the index patient was analyzed by next generation sequencing of the AGL gene. For confirmation of the two mutations found, genetic analysis of the parents and grandparents was also performed. The patient was compound heterozygous for the novel mutation c.3235C>T, p.Gln1079⁎ (exon 24) and the known mutation c.1589C>G, p.Ser530⁎ (exon 12). c.3235 >T, p.Gln1079⁎ was inherited from the father, who inherited it from his mother. c.1589C>G, p.Ser530⁎ was inherited from the mother, who inherited it from her father. Conclusion. We report the first genetically confirmed case of a Romanian patient with GSDIIIa. We detected a compound heterozygous genotype with a novel mutation, in the context of a severe hepatopathy and an early onset of cardiomyopathy.